PERAN CYBERVETTING DALAM PENGAMBILAN KEPUTUSAN REKRUTMEN CALON KARYAWAN - Zain, Tsurayya Syarif; Fakhriya, Siti Dini (Psyche: Jurnal Psikologi, 2023)
Human Resources (HR) management in a company is inseparable from the importance of managing the recruitment process in accepting new prospective employees. One of the methods used in selecting employee candidates is through a cyber-vetting process on social media. Cybervetting is checking information and data of prospective candidates as well as individual internet reputation through search engines such as Google and social media (Facebook, Twitter, Instagram, and Linkedin). Based on this background, this study aims to determine cyber-vetting on employee recruitment decision-making. This research uses the descriptive research method. Respondents in this study are people who work in the field of recruitment both as internal company recruiters and third-party recruiters in companies domiciled in South Sumatra. The instrument in this study was an online questionnaire. A total of 12 respondents from 12 companies in South Sumatra filled out the online questionnaire. The study results show that most recruiters conduct a personal assessment of their prospective employees through social media or cyber-vetting. Therefore, social media should be used as a medium that positively impacts its users and knows the importance of paying attention to digital footprints by reflecting professionalism and good social media behavior to create trust for recruiters.